Pemanfaatan Pupuk Hayati Trichoderma sp. Untuk Meningkatkan Pertumbuhan dan Produksi Kacang Kedelai (Glycine max L.) Serta Pengendalian Hama dengan Pestisida Nabat - Rambe, Merryana Christien; Sijabat, Octanina Sari; Kurniawan, Dedi (Universitas Teuku Umar, 2024)
This study aims to evaluate the effect of a combination of biofertilizer and vegetable pesticide applications on the growth and yield of soybean. The research was conducted in Selayang Village, Selesai District, Langkat Regency, North Sumatra Province from December 2023 to March 2024. Using a factorial Randomized Group Design (RAK) design, this study considered several parameters such as plant height, number of leaves, flowering age, and seed production. Results showed that the application of biofertilizers had a significant effect on several growth and production parameters, while the application of plant-based pesticides also had a different impact on several parameters. The interaction between the two factors was also shown to have an effect on plant height, number of pods, and seed weight. The best treatment combination was S2P1 (biofertilizer 75 grams/polybag) and (vegetable pesticide once a week).Keywords: Biological fertilizers, vegetable pesticides, soybeans.